PENGARUH KONSELING KESEHATAN TERHADAP PENGETAHUAN MASYARAKAT TENTANG GASTRITIS DI WILAYAH KERJA PUSKESMAS TULEHU KABUPATEN MALUKU TENGAH - Rusli Taher; Alfrinli Frelisye Palpialy; Nurhikmah; Andi Sulfikar; Ahmad Mushawwir (Stikes Graha Edukasi Makassar, 2023)
Background: Gastritis is a disease that is often found in clinics or internal medicine rooms and is a disease that many people complain about, both teenagers and adults. Objective: to determine the effect of health counseling on public health knowledge about gastritis at the Tulehu Health Center, Central Maluku Regency. Design: The research design used was Pre-Experimental. Results: Obtained before counseling that did not know gastritis 23 respondents (71.9%), and after counseling did not know gastritis 9 respondents (28.1%). p value = 0.362. Conclusion: From this study there is an effect of health counseling on community knowledge about gastritis in the work area of ??the Tulehu Health Center, Central Maluku Regency. Suggestion: For health workers to further improve counseling through discussions, lectures, and health workers must further improve a number of cognitive, affective, cognitive parameters for respondents about gastritis